Sabbatical leave report: Fall 2014 - Cardone, Resha (2014)
Cardone wrote chapters of a book manuscript and submitted two related articles to peer reviewed journals. She also transcribed and edited a scholarly interview, presented portions of book project at conference and traveled to site of book topic for on-ground research. Accomplishments are different than outlined in original proposal. The report describes project issues and results. Book title is "Unbound and underground: Chile's Ergo Sun Project from the dictatorship to the digital era."
Keywords: dept.wll; faculty_collection; sabbatical_report

Unbound and Underground: Chile's Ergo Sun Project from the Dictatorship to the Digital Era - Cardone, Resha (2014)
Cardone wrote chapters of a book manuscript and submitted two related articles to peer reviewed journals. She also transcribed and edited a scholarly interview, presented portions of book project at conference and traveled to site of book topic for on-ground research. Accomplishments are different than outlined in original proposal. The report describes project issues and results.
Keywords: dept.wll; faculty_collection; sabbatical_report

The Minor Tone of Desire - Barros, Pía; Cardone, Resha (Ediciones Sherezade, 2018)
Keywords: 21st century; Chilean fiction; Translations into English; Translations into English; Chilean fiction; Women authors; dept.wll; faculty_collection